High-speed end-milling of AISI 304 stainless steels using new geometrically developed carbide inserts - Abou-El-Hossein K.A.; Yahya Z. (2023)
AISI 304 stainless steel possesses some properties, such as low thermal conductivity and high ductility that make them be classified under materials of poor machinability that exhibit a lot of difficulties during cutting. This work reports an experimental study on the performance of multilayered (TiN/TiCN/TiN) carbide inserts recently developed for end-milling of AISI 304 stainless steels. The length of chip-tool contact is small for these inserts as they contain a chip breaker that restricts the chip-tool contact area. In this study, the possible failure modes of tool wear were discussed and the effect of cutting speed and feed rate variation on tool life and tool wear modes was investigated. An increase in tool wear was noticed with increasing the cutting speed, while at the same time, a decrease in tool wear was observed with increasing the cutting feed. The most optimum cutting parameter for end-milling operation using a single end mill was established in terms of maximum productivity and maximum tool life. 2005 Elsevier B.V. All rights reserved.